EFEKTIVITAS PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS XI KEUANGAN SMK NEGERI 2 JAYAPURA TAHUN PELAJARAN 2013/2014 - Oetama, Welmina (Magister Pendidikan IPA, UNCEN, 2015)
This study aimed to determine: (1) distinction of student learning result who followed problem based learning model with direct instructional, (2) the differences of students result learning in interest money who has higher motivation, medium, and poor in learning, (3) there is interaction of learning model with motivation level across from student learning result. This experimental study using two groups, as experimental group using problem based learning model and control group using direct instructional model. The study sample was 54 students. The instrument consisted of test and the questionnaire of motivation. To collect data from student learning result after they have test and result from the questionnaire of motivation. All data were analysed and tested by statistic parametric univariate test (ANAVA) using SPSS version 16.0. From three proposed hypothesis the result showed that: (1) there is significantly different between problem based learning model with direct instructional model, value sig 0,014 < Î± 0,05, (2) there is significantly interaction between student learning result in interest money with the level of student motivation in learning, value sig 0,013 < Î± 0,05, (3) there is no interaction between the model of learning with the students level of motivation, value sig 0,601 > Î± 0,05. Keywords: Problem based learning, Student learning result, Interest money, Motivation to learn.